Development of Equation Oriented Modelling of Advanced Distillation Process Using MOSAIC: Dividing Wall Column Case study - Rosshila, Idris; C. T., Hing; Noorlisa, Harun; Mohamad Rizza, Othman (AENSI Publishing, 2017)
This paper presents the development of an equation oriented models of chemical processes using MOSAIC. MOSAIC is a web-based modelling software developed by Dynamic and Operation of Technical Plants of TU Berlin. It provides a new platform which can be used as an alternative to the current approach of modeling using programing languages. MOSAIC is particularly useful in developing custom models of process unit operation that is not readily available in sequential modular based process simulators. MOSAIC allow users to develop models, generate the models' code and translate the model into different environments i.e. gPROMS, Aspen custom Modeler (ACM), Matlab etc. To shows its efficiency, a dividing wall column (DWC) for oleochemical fatty acid (FA) fractionation were modelled. A step by step approach to the modelling using MOSAIC is shown. The results are in agreement with data from steady state simulation in Aspen Plus and indicate that MOSAIC is a good modelling environment tool. Furthermore, the modelling effort is made possible even without the knowledge of programming languages. In addition, a comparison with another modelling environment (gProms, ACM, C++, Fortran) is highlighted which is useful in aiding researchers to choose MOSAIC for any modelling works